One remark concerning double-infinite Toda lattice - Berezansky, Yu. M. (Methods of Functional Analysis and Topology, 2012)
We propose the power moment approach to investigation of double-infinite Toda lattices, which was contained in author’s article [6]. As a result, we give the main theorem from [6] in a more effective form.